Sistem Monitoring Kadar Gas Berbahaya Pada Lokasi Parkiran Bawah Tanah Menggunakan Protokol MQTT - Loki Sudiarta Mongin; Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In general, parking buildings are part of a building where activity centers such as shops and offices are used specifically as temporary parking spaces for vehicles, during activities in the building. Limitations and availability of open space and vacant land in the vicinity of these buildings, the selection of parking locations on the basement and upper ground is the main choice, but this location selection often makes building designers and developers ignore the interests of the air duct which serves as a place for exchanging fresh air and pollutant gases in the parking area so that the air change ratio (ACH) is in the danger threshold for the workers and users of the parking facility, especially in the basement parking area with the most exhaust gas air pollution from the entry and exit of motorized vehicles. Referring to the description of the problem, the authors made a monitoring system of dangerous pollutant gas levels found in underground parking locations using MQTT-based lightweight communication protocol using the ESP8266 wifi module. In this system there are also MQ-7 and MQ-135 sensors which serve as an early detection device for changes in levels of carbon monoxide and nitrogen oxide gases which are then processed by the Arduino Uno microcontroller to obtain data processing in json format which is then sent to the web server in this case, thingsboard.io to be displayed in the form of graphs and charts so that it can be more easily monitored by users who need a reading of changes in the level of pollutant gas in that location. From the results obtained after this system runs as a whole, the system requires time to process data ranging from 1.3 - 1.5 seconds while for sending data to the web server is taken within a period of 2 second.